Reusable framework for web application development - Samingan, Mohd. Razak (2017)
Web application (WA) is among the mainstream enterprise-level software solutions. One of the reasons for this trend was due to the presence of Web application framework (WAF) that in many ways has helped web developer to implement WA as an enterprise system. However, there are complexity issues faced by the developers when using existing WAFs as reported by the developers themselves. This study is proposed to find a solution to this particular issue by investigating generic issues that arise when developers utilize Web as a platform to deliver enterprise-level application. The investigation involves the identification of problems and challenges imposed by the architecture and technology of the Web itself, study of software engineering (SE) knowledge adaptation for WA development, determination of factors that contribute to the complexity of WAF implementation, and study of existing solutions for WA development proposed by previous works. To better understand the real issues faced by the developers, handson experiment was conducted through development testing performed on selected WAFs. A new highly reusable WAF is proposed, which is derived from the experience of developing several WAs case studies guided by the theoretical and technical knowledge previously established in the study. The proposed WAF was quantitatively and statistically evaluated in terms of its reusability and usability to gain insight into the complexity of the development approach proposed by the WAF. Reuse analysis results demonstrated that the proposed WAF has exceeded the minimum target of 75% reuse at both the component and system levels while the usability study results showed that almost all (15 out of 16) of the questionnaire items used to measure users’ attitudes towards the WAF were rated at least moderately by the respondents.